Controles internos e gestão de riscos: Instrumento de eficiência dos jurisdicionados do Tribunal de Contas do Estado do Ceará - Almeida, Adriana Maria Pinheiro de (2018)
Public institutions exist to serve society. These services need to be quality, with universal benefits at great cost, leading institutions to seek to improve their practices. As a result, risk management and internal control activities become increasingly important in achieving the objectives and goals of these institutions, thus serving as an instrument for the efficiency of these entities. This present research has as main purpose to analyze the internal control struc-ture of the State organs of Ceará in the perspective of the Risk Management, according to the Normative Instruction TCE / CE nº 03/2015, adopting the quantitative approach, developed through descriptive analysis of the data and elaboration of an econometric model to mark the interpretations extracted from the self-evaluation form of the internal control, for the year 2016, applied by the TCE / CE to its jurisdictions. The research sample consisted of 61 State Administrative Units, grouped as follows: 39 organs, 9 Autarchies, 10 Societies of Mixed Economy and 3 Foundations. It is concluded that the internal control system provided, in ac-cordance with a recognized methodology in terms of risk management, is effectively an in-strument of efficiency for the jurisdictions, by providing means for the institutional objectives to be fulfilled, minimizing the risks of errors and irregularities, thus contributing to the pro-motion of efficiency.